2018
DOI: 10.1038/s41534-018-0081-3
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Bell’s inequalities into state classifiers with machine learning

Abstract: Quantum information science has profoundly changed the ways we understand, store, and process information. A major challenge in this field is to look for an efficient means for classifying quantum state. For instance, one may want to determine if a given quantum state is entangled or not. However, the process of a complete characterization of quantum states, known as quantum state tomography, is a resource-consuming operation in general. An attractive proposal would be the use of Bell's inequalities as an enta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 54 publications
3
41
0
Order By: Relevance
“…Previous work on using machine learning for the separability problem has been focused either having the machine choose good measurements and then using an existing entanglement criteria [25,26] , or on viewing the task as a classification problem [27][28][29][30][31][32][33]. For classification, typically a training set is constructed where quantum states are labeled as separable or entangled.…”
Section: Related Workmentioning
confidence: 99%
“…Previous work on using machine learning for the separability problem has been focused either having the machine choose good measurements and then using an existing entanglement criteria [25,26] , or on viewing the task as a classification problem [27][28][29][30][31][32][33]. For classification, typically a training set is constructed where quantum states are labeled as separable or entangled.…”
Section: Related Workmentioning
confidence: 99%
“…We will then consider different possible applications of quantum reservoir networks. It should be noted that while many important works in the field of quantum machine learning aim to use classical neural networks to optimize quantum setups [ 38–43 ] or process the results of quantum experiments, [ 44–48 ] the entities of quantum reservoir networks are themselves quantum. As quantum systems, quantum reservoir networks can result in performance advantages for classical tasks and have an enhanced memory capacity, as we will discuss in Section 3.…”
Section: Introductionmentioning
confidence: 99%
“…Sirui Lu and co-workers have shown the separability criteria of entangled state using convex hull approximation and supervised learning [18]. Ma and Yung showed that it is possible to classify the separable and entangled states using artificial neural networks [19]. The work has been further extended to experimental data [20] and later has been applied to simultaneous learning of multiple nonclassical correlations as well [21].…”
Section: Introductionmentioning
confidence: 99%